Will Germany's Temporary VAT Tax Rates Cut as Part of the Covid-19 Fiscal Stimulus Package Boost Consumption and Growth? - Michael Funke; Raphael Terasa (Center for Economic Studies and Ifo Institute (CESifo), 2020)
On 3 June 2020, the German government announced a EUR 130 billion fiscal stimulus package to stimulate market demand and jumpstart the economy in the wake of the COVID-19 pandemic lockdown in the spring of 2020. The most prominent measure of this package is an unconventional fiscal policy in the form of a temporary VAT rates cut for six months, from 1 July to 31 December 2020. Employing a dynamic stochastic general equilibrium (DSGE) framework, we study the efficiency of the VAT tax rates cut for ameliorating the consequences of the pandemic recession. The simulation of the calibrated DSGE model yields a tax policy-induced real GDP increase of about 0.3 percentage points for 2020.
Keywords: E30; E60; H25; I15; 330; fiscal policy; value-added tax; DSGE model; Covid-19; Germany